Retrospective analysis of poisoning cases admitted in a tertiary care hospital in North Eastern UP, India - R.R. Singh; Anoop Kumar; Dharmendra Uraiya; Pooja Dhaon (International Journal of Medical Research and Review, 2016)
Aims: Poisoning is a medical emergency associated with significant morbidity and mortality. This study was done to analyse the pattern of poisoning cases coming to our tertiary care centre located in the north eastern part of U.P., India. It is important to know the pattern of poisoning in a region so as to take proper actions for prevention and management of the cases.Methods: This was a retrospective hospital record based study of poisoning patients who were admitted to our tertiary care hospital between July, 2014 to December 2015. Data of total 140 cases were analyzed for demography, type of poisoning and outcome and results were analyzed statistically.Results: Pesticides dominated the picture amongst the rural population while urban people consumed drugs and household agents. The overall mortality rate was 4.28%. Most of the deaths were in Aluminium phosphide cases (66.66%) followed by paraquat and organochlorine.Conclusion: In adults poisoning is mostly suicidal while children accidentally ingest substances. Pesticides, chemicals and drugs available in house are mostly used. Rural people resort to pesticides while urban population takes household articles or drugs for self harm. Mortality depends on the type of poison, amount consumed and the time lapsed in reaching a health care facility as well as how equipped is the health care facility to tackle the poisoning cases.